Mathematics teachers’ practices in light of the effective teaching practices - Awaji, Bakri M.; Abdel-Hamid, Rasha Hashim; Khalil, Ibrahim Alhussain; Prahmana, Rully Charitas Indra (IKIP Siliwangi and I-MES, 2025)
Recognising the pivotal role of effective teaching practices in enhancing student learning outcomes, the National Council of Teachers of Mathematics (NCTM) has outlined a comprehensive framework of key strategies. However, empirical research on these practices remains limited. Therefore, this study aimed to investigate the extent to which mathematics teachers apply NCTM-identified effective teaching practices and examine potential differences attributable to teachers' gender and teaching experience. Adopting a quantitative approach and employing a descriptive survey, the study systematically assessed eight designated practices using a validated observation checklist in the Jazan Education Administration, observing 38 mathematics teachers during routine classes. The results indicated a moderate level of implementation overall, with ten practices demonstrating high application. Statistical analyses found no significant differences in practice implementation based on gender or teaching experience at the .05 level. The limitations included the study's relatively small sample size, potentially limiting generalisability, and the observational nature of the checklist, which may not fully capture nuanced teaching dynamics. Future research could focus on developing training initiatives to enhance educators' application of NCTM-recommended practices and undertake qualitative inquiries to understand barriers to integration and teachers' attitudes towards these practices. Finally, this study contributes to the discourse on effective mathematics teaching by providing empirical insights into current practices and highlighting avenues for further investigation and professional development in educational settings.